Electronic and thermoelectric properties of the layered BaFAg Ch ( Ch = S, Se and Te): First-principles study - Boudiaf, Khaouther; Bouhemadou, Abdelmadjid; Al-Douri, Yarub; Khenata, Rabah; Bin-Omran, Saad; Guechi, N. (Elsevier, 2018)
By using the full potential linearized augmented plane wave (FP-LAPW) method, the electronic properties of the layered BaAgChF (Ch = S, Se, Te) were investigated. Both the standard GGA and the TB-mBJ potential were used to model the exchange-correlation potential. To evaluate the spin-orbit coupling (SOC) effect, both the scalar relativistic and full relativistic calculations were performed. The SOC effect is found to be not negligible in the title compounds. The FP-LAPW band structure and the semi-classical Boltzmann transport theory were used to study the charge-carrier concentration and temperature dependences of the thermoelectric parameters, including Seebeck coefficient, electrical conductivity, thermal conductivity and figure of merit. Our results show that the values of the thermoelectric parameters of the p-type compounds are larger than that of the n-type ones. The optimal p-type doping concentrations and temperatures that yield the maximum values of the figure of merit of the title compounds were calculated. These are important parameters to guide experimental works.